Recording Voiceover : the Spoken Word in Media - Blakemore, Tom (Focal Press, 2015)
The only book on the market to specifically address its audience, Recording Voiceover is the comprehensive guide for engineers looking to understand the aspects of capturing the spoken word. Discussing all phases of the recording session, Recording Voiceover addresses everything from microphone recommendations for voice recording to pre-production considerations, including setting up the studio, working with and directing the voice talent, and strategies for reducing or eliminating distracting noise elements found in human speech. Recording Voiceover features in-depth, specific recommendations f.